Fungal literature records database of the sub-Antarctic Region of Aysen, Chile - Sanchez Jardon, Laura; del Rio-Hortega, Laura; Cea, Noemi Nunez; Mingarro, Mario; Manubens, Paloma; Zambrano, Sebastian; Gallo, Belen Acosta (My University, 2021)
To this day, merely 8% of all estimated fungi species are documented and, in certain regions, its biodiversity is practically unknown. Inside the Fungi Kingdom, macrofungi and lichens assume a critical part in the ecosystem functionality and have a historical connection to mankind's social, clinical and nutritious uses. Despite their importance, the diversity of these groups has been widely overlooked in the sub-Antarctic Region of Chile, a crucial area in the study of climate change due to its extraordinary biodiversity and its proximity to Antarctica. Few studies regarding both groups have been conducted in this sub-Antarctic Region and the data are still scarce and inaccessible, as these are only published in specialised journals, unreachable to local communities. This publication presents a records compilation available in previous published scientific and technical reports on macrofungi and lichen diversity. In total, 1263 occurrence records of 618 species (341 records of 251 macrofungi species and 922 records of 367 lichen species) were digitised and integrated into the regional platform Biodiversity Information System for Aysen (SIB-Aysen) and into GBIF. Here, we provide the fullest dataset on one of the most diverse group of living beings in one of the the least-known world regions.
Keywords: chilean patagonia; macrofungi; lichens; mycobiota; sib-aysen; gbif